Subjective Probability and the Prisoner's Dilemma - Wilson, John G. (Management Science, 1986)
The paradox involved in sequences of Prisoner's Dilemma games is due to the fact that game theoretic definitions of optimality rarely coincide with any natural meaning of the word. Decision makers should incorporate their beliefs and experience into any mathematical analysis of the games. Once this has been done, via subjective probabilities, use of the cooperative move in iterated Prisoner's Dilemma games can often be justified. The paper provides a simple algorithm for determining an optimal strategy, once the decision maker's subjective probabilities have been specified.